2017
DOI: 10.1021/acsami.7b09884
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Microsphere-Embedded Film for Microsphere-Enhanced Raman Spectroscopy

Abstract: Dielectric microspheres with extraordinary microscale optical properties, such as photonic nanojets, optical whispering-gallery modes (WGMs), and directional antennas, have drawn interest in many research fields. Microsphere-enhanced Raman spectroscopy (MERS) is an alternative approach for enhanced Raman detection by dielectric microstructures. Unfortunately, fabrication of microsphere monolayer arrays is the major challenge of MERS for practical applications on various specimen surfaces. Here we report a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Anderson has drop‐casted silica microspheres onto a glass substrate and deposited the analyte on top achieving the highest enhancement in the contact area of two neighboring microspheres. Other materials and configurations have been used, such as single polystyrene sphere or layer of polystyrene spheres, BaTiO 3 microsphere‐embedded film, or multilayers of T‐rex shell spheres …”
Section: Introductionmentioning
confidence: 99%
“…Anderson has drop‐casted silica microspheres onto a glass substrate and deposited the analyte on top achieving the highest enhancement in the contact area of two neighboring microspheres. Other materials and configurations have been used, such as single polystyrene sphere or layer of polystyrene spheres, BaTiO 3 microsphere‐embedded film, or multilayers of T‐rex shell spheres …”
Section: Introductionmentioning
confidence: 99%
“…The emission in the divergent angle of 30° demonstrated an anisotropic and non‐Lambertian far‐field profile. The contribution of the DA effect to PL enhancement is expressed as [ 37–41 ] ERInormala=2π1cossin1NA||EMCθ2normaldΩ2π1cossin1NA||EPeMCθ2normaldΩ where | E PeMC (θ)| and | E MS (θ)| are the angle‐dependent far‐field electric intensity profiles from a PeMC without/with an MS cavity, respectively. According to Equation (), ERI a was estimated to be 5.10.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35,36 ] Our previous studies have demonstrated three major properties of microsphere (MS) as an optical cavity for optical manipulation, i.e., Mie focusing (MF), whispering‐gallery mode (WGM), and directional antenna (DA). [ 37–41 ] Excitation light incident into the MS can be focused by Mie resonance down to Abbe's diffraction limit, by which the excitation intensity at the MS shadow side is dramatically enhanced. [ 42,43 ] The scattered light in the vicinity of MS can be trapped as WGMs resonated in the MS cavity, by which the optical state density was tailored to facilitate the SR decay rate via Purcell effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photonic properties of a microsphere are illustrated in the Supplementary Information. They were used in optical data extraction [21], Raman spectroscopy measurements [22,23], enhancement of luminescence collection [24,25,26], super-resolution microscopy [27,28,29] and many other fields. Still the use of microspheres for quantum emitters nano-spectroscopy has not yet demonstrated or tested, despite the raising interest in quantum communication and information emerged in the last few years.…”
mentioning
confidence: 99%